Удосконалення технології вирощування столових буряків з модернізацією сівалки VESTA 8 PROFI - Колісник, Владислав Валентинович; Kolisnyk, Vladyslav (ЦНТУ, 2023)
Робота спрямована на удосконалення технології вирощування столових буряків та підвищення якості роботи сівалки VESTA 8 PROFI. Проаналізовано існуючі технологіївирощування столових буряків. На підставі проведеного аналізу обґрунтовані удосконалення технології вирощування цієї культури з врахуванням сучасної техніки та технологій проведення операцій. В інженерній частині проведені розрахунки параметрів висівного апаратасівалки VESTA 8 PROFI. Запропоновані удосконалення дозволяють збільшити продуктивність посівного агрегату та зменшити витрати палива при цьому. The work is aimed at improving the technology of growing table beets and improving the quality of the VESTA 8 PROFI seeder. The existing technologies for growing table beets are analyzed. On the basis of the conducted analysis, the improvement of the cultivation technology of this crop is substantiated, taking into account modern equipment and technologies of conducting operations. In the engineering part, the parameters of the sowing device of the VESTA 8 PROFI planter were calculated. The proposed improvements make it possible to increase the productivity of the sowing unit and reduce fuel consumption at the same time.
Improving the technology of growing red beets with the modernization of VESTA 8 PROFI planter
Keywords: технологія вирощування; столові буряки; диск висівного апарата; cultivation technology; table beets; seeder disc